Economic Inclusion of LGBTI Groups in Thailand - World Bank (World Bank, Washington, DC, 2022)
Thailand is widely considered progressive among developing and middle-income countries regarding the inclusion of lesbian, gay, bisexual, transgender, or intersex (LGBTI) people. Yet, a growing body of research shows they still experience discrimination, limited job and housing opportunities, and barriers to accessing many common services. Most information on sexual orientation and gender identity (SOGI) in Thailand is qualitative in nature. A new study led by the World Bank, in partnership with Thammasat University, Love Frankie, and the Nordic Trust Fund, includes the first endeavor to gather and analyze quantitative data on economic and financial outcomes for a large, statistically significant sample of LGBTI people in Thailand. Qualitative data from in-depth ‘live story’ interviews with 19 SOGI-diverse participants from across each of Thailand’s main regions complement the online survey data and provide further insights into the lives of LGBTI respondents. For the first time in Thailand, the study also presents information on non-LGBTI people and their attitudes toward LGBTI groups, based on survey responses from a statistically representative non-LGBTI reference group. The study focuses on how LGBTI people fare in Thai society economically and financially: their opportunities and inclusion, or discrimination and exclusion. It highlights outcomes for the LGBTI and non-LGBTI population in the labor, housing, and financial markets, along with LGBTI people’s challenges in their access to education, health, and government services. Based on the study’s results, international experience, and literature reviews, the report offers policy and programmatic options to widen opportunities for the LGBTI population and share prosperity among all the people in Thailand.